The emperor of all maladies: a biography of cancer - Mukherjee, Siddhartha (London, 2011)
"The Emperor of All Maladies is a magnificent, profoundly humane "biography" of cancer—from its first documented appearances thousands of years ago through the epic battles in the twentieth century to cure, control, and conquer it to a radical new understanding of its essence. Physician, researcher, and award-winning science writer, Siddhartha Mukherjee examines cancer with a cellular biologist's precision, a historian's perspective, and a biographer's passion. The result is an astonishingly lucid and eloquent chronicle of a disease humans have lived with -and perished from- for more than five thousand years. The story of cancer is a story of human ingenuity, resilience, and perseverance, but also of hubris, paternalism, and misperception. Mukherjee recounts centuries of discoveries, setbacks, victories, and deaths, told through the eyes of his predecessors and peers, training their wits against an infinitely resourceful adversary that, just three decades ago, was thought to be easily vanquished in an all-out "war against cancer." The book reads like a literary thriller with cancer as the protagonist. From the Persian Queen Atossa, whose Greek slave cut off her malignant breast, to the nineteenth-century recipients of primitive radiation and chemotherapy to Mukherjee's own leukemia patient, Carla, The Emperor of All Maladies is about the people who have soldiered through fiercely demanding regimens in order to survive -and to increase our understanding of this iconic disease."